PENGARUH INTELLECTUAL CAPITAL TERHADAP KINERJA KEUANGAN BADAN LAYANAN UMUM (BLU) UIN SYARIF HIDAYATULLAH JAKARTA - Ady Cahyadi; Nur Wachidah Yulianti; Husnul Khotimah; Yudi Setiadi (Universitas Sarjanawiyata Tamansiswa, 2020)
This research purpose investigates the influence of intellectual capital, as measured by VAICTM that consist of three components of firms’ resources (human capital, structural capital, and capital employed) to financial performance of Syarif Hidayatullah State Islamic University of Jakarta. This research used SEM PLS as tool for test and data analyze. Result of this research showed that of the seven items were tested in the proxy as financial performance, only three of them that can be processed. They were Fixed Asset Turnover, Return On Assets and Return On Equity. Result of hypothesis testing showed intellectual capital (VAICTM) significantly influence to financial performance of Syarif Hidayatullah State Islamic University of Jakarta.